ChemInform Abstract: Zero Thermal Expansion and Ferromagnetism in Cubic Sc1‐xMxF3 (M: Ga, Fe) over a Wide Temperature Range. Issue 7 (29th January 2015) - Hu, Lei; Chen, Jun; Fan, Longlong; Ren, Yang; Rong, Yangchun; Pan, Zhao; Deng, Jinxia; Yu, Ranbo; Xing, Xianran
Abstract The compounds ScF3, (Sc0.95Ga0.05)F3, (Sc0.9Ga0.05Fe0.05)F3, (Sc0.85Ga0.05Fe0.1)F3, and (Sc0.8Ga0.05Fe0.15)F3 are prepared by solid state reaction of Sc2O3, Fe2O3, Ga2O3, and NH4F (Pt crucible, 600 °C, 5h).